Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 4517 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Bombus humilis Illiger, 1806", "Geometry POLYGON((-46.93 -7.84,-46.93 78.67,173.50 78.67,173.50 -7.84,-46.93 -7.84))", "HasGeospatialIssue is false" ] } The dataset includes 4517 records from 50 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0015689-160311141623029/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences